Evaluation of sensory and in vitro anti-thrombotic properties of traditional Greek yogurts derived from different types of milk. Issue 1 (January 2017) - Megalemou, Kalliopi; Sioriki, Eleni; Lordan, Ronan; Dermiki, Maria; Nasopoulou, Constantina; Zabetakis, Ioannis
Abstract: Given that fermented dairy products exhibit high bioactivities against cardiovascular diseases (CVDs), the anti-thrombotic properties, fatty acid profiles and sensory properties of cow, goat and ewe derived Greek yogurts have been assessed and compared. The total lipids (TL), total polar lipids (TPL), total neutral lipids (TNL) were obtained and the polar lipid fractions were further separated by thin layer chromatography (TLC). These lipid samples (TL, TPL and TLC fractions) were subsequently assessed for their biological activity against atherosclerosis based on the in vitro inhibition of Platelet Activating Factor (PAF)-induced platelet aggregation. The fatty acid compositions of all yogurts were analyzed by Gas Chromatography with flame ionization detector (GC-FID). Goat yogurt lipids have been found to exert more potent inhibitory activity (i.e. lower IC50 values in both TL and TPL samples) in contrast to the corresponding fractions of cow and ewe yogurts. The observed sensory data indicates that ewe yogurt was the most palatable of all three Greek yogurts.